The effect of Tumor Necrosis Factor alpha inhibitor on wound healing of oral mucosa in induced diabetic rats - Maroof, Rafah Al-; Fareed, Farhad F. (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Impaired wound healing is a major complication of diabetes mellitus. This study was carried out to determine the healing process of oral mucosa in diabetic rats and the role of systemic tumor necrosis factor alpha inhibitor (infliximab). Methods: Thirty eight male rats were divided into two groups, the normoglycemic group (11 rats), and diabetic group (27 rats) that were rendered diabetic by alloxan injection. Two months later, wound was created in the lateral side of the tongue for both groups. The diabetic group was then subdivided into two subgroups, 14 rats received 5mg/kg infliximab subcutaneous injection at the day of wound creation while the other 13 rats received saline injection. After 7 days, biopsies of the tongue were collected and subjected to histological and histochemical procedure. Results: Histological examinations showed delayed healing in the diabetic group with persistence of epithelial discontinuity, large amount of granulation tissue and destruction of the underlying muscle fibers. In the subgroup injected with infliximab, reepitheliazation of the wound was demonstrated with well arranged underlying collagen fibers. Using PAS stain, diabetic group revealed a dramatically high amount of PAS positive precipitants in the lamina properia, especially in the wall of the blood vessels, while with infliximab injection, the PAS+ve precipitants were more prominent than normoglycemic group but less than diabetic group without infliximab. Conclusion: These findings suggest that infliximab accelerated mucosal wound healing in the diabetic rats with the formation of well organized connective tissue.